The Study on Liquid Soap Production from Recycled Frying Oil (The Effect of Mixing Time and Water:Soap Ratio on the Quality) - Wijana, Susinggih; Soemarjo, Soemarjo; Harnawi, Titik (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
The aim of this study is to find out the best combination treatment of the processing of liquid soap from recycled frying oil. The process step of refining was as follow: steaming with ratio water to oil of 1:1 (w/w), neutralization with NaOH 4N, and bleaching with bentonit 0,84% (w/w). The factorial experiment was employed by Randomized Block Design, mixing time (60, 90 and 120 minutes) was the first factor, and water/soap ratio (2:1; 3:1 and 4:1 w/w) was second factor. Analysis on the product included pH, residual of free alkali, foam ability, viscosity, fatty acid total, and the sensory evaluation was conducted on the appearance, viscosity, foam ability, astringency, and aroma. The results showed that the best combination treatment achieved by mixing time of 90 minutes and water/soap ratio of 2:1 w/w. The liquid soap had characteristics of pH value of 10.07, residual free alkali of 0.03%, foam ability of 2,03 cm, viscosity of 5.20 cps, and residual fatty acid of 8.60%, and the organoleptic evaluation indicated that the product had the preference of appearance of 3.27 (neutral), viscosity of 2.97 (less preferred), foam ability of 2.4 (less preferred), astrigency of 3 (neutral), and aroma of 3.87 (neutral).Keywords: liquid soap, mixing, water/soap ratio, recycled frying oil, refining